Types of Peer Written Corrective Feedback on Recount Text in EFL Class (RETAIN, 2019)
Abstrak Setiap jenis umpan balik korektif tertulis yang dibuat oleh teman sejawat telah berkontribusi pada peningkatan keterampilan menulis siswa. Dengan demikian, peneliti menemukan jenis umpan balik korektif tertulis yang dibuat oleh rekan dan alasan memilih jenis tersebut. Penelitian ini adalah studi kasus. Subjek penelitian adalah 34 siswa kelas 10 SMA Negeri 1 Rejoso. Instrumen penelitian adalah umpan balik tertulis dan pedoman wawancara siswa. Peneliti mengambil data melalui umpan balik tertulis siswa, wawancara kelompok, dan wawancara mendalam. Hasil penelitian menunjukkan ada 2 jenis yang ditemukan dalam umpan balik tertulis siswa; umpan balik tidak langsung yang tidak dikodekan dan umpan balik reformulasi. Alasan siswa dikategorikan ke dalam dua kategori; kepraktisan memberi umpan balik dan peningkatan diri siswa. Para siswa mempertimbangkan kepraktisan dalam memberikan umpan balik dan visibilitas menggunakan tanda. Menjadi pembelajar mandiri dan meningkatkan kesadaran siswa adalah alasan siswa yang mengarah pada peningkatan diri siswa.Kata kunci: Jenis umpan balik korektif tertulis, umpan balik teman sejawat, hasil tulisan siswa EFL Abstract Each types of written corrective feedback made by peer had contributed to students’ improvement in writing skills. Thus, the researcher found out the types of written corrective feedback made by peers and the reason for choosing those types. This study is a case study. The subject was 34 students from 10th graders of SMA Negeri 1 Rejoso. The research instruments are students’ written feedback and interview guideline. The researcher took the data through students’ written feedback, group interview, and deep interview. The result of the study shows there are 2 types found in students’ written feedback; uncoded indirect feedback and reformulation feedback. The students’ reasons are categorized into two categories; the practicality of giving feedback and student self-improvement. The students are considering the practicality of giving feedback and the visibility of using signs. Being an independent learner and increasing students’ awareness is students’ reason which led to student self-improvement. Keywords: Types of written corrective feedback, peer feedback, EFL learners’ writing